Radiative simulation of non-Newtonian MHD fluid over a boundary-driven multi-physical curved mechanism: Keller–Box evidence - Sanni, Kehinde M.; Asghar, Saleem; Al-Shbeil, Isra; Cătaş, Adriana (Frontiers in Physics, 2023)
This study is numerically driven to ascertain the flow of two-dimensional heat transfer of an incompressible electrically conducting non-Newtonian fluid over a continuous power-law stretching curved surface. The flow model considers rheological fluid viscosity using curvilinear (r-, s-) coordinates. Energy equation for the curved sheet is examined in two streams; the prescribed surface temperature and prescribed heat flux. Surface frictional heating is influenced by thermal radiation and viscous dissipation. Similarity transformations is executed in reducing partial differential equations into ordinary differential equations. Keller-Box shooting method together with jacobis iterative techniques is numerically computed for the degenerated nonlinear system of boundary value problem. The associated boundary-layer thickness and flow fields- velocity and temperature are analyzed against characterising parameters. Significant results are obtained and discussed with graphical plots showing that fluid velocity can be controlled by virtue of fluid parameters and stretching power index. These results are useful in polymer dynamics involving melting and manufacturing of stretchable sheets.